Pengelolaan Kelas dan Pemanfaatan Sumber Belajar terhadap Prestasi Belajar pada Mata Pelajaran Ekonomi: The Influence of Classroom Management and Utilization of Learning Resources on Learning Achievement in Economics Subjects - M. Saipul Watoni (Pendidikan Al-Gafari, 2026)
Classroom management is an effort to create a comfortable learning atmosphere in the classroom during the teaching and learning process, mutually beneficial for both students and teachers. Good classroom management can optimally achieve learning objectives, both instructional and supplementary. Learning resources, such as guidebooks or textbooks that support the teaching and learning process, also focus on the environment inside and outside the classroom, teachers, learning facilities and infrastructure, and many others. The use of learning resources is also part of achieving educational quality. The goal is to determine the effect of classroom management and the use of learning resources on student achievement. The data collection technique was conducted by questionnaire. This type of research is ex post facto. From the multiple linear regression equation, it has a positive value on the constant, namely 40.451, stating that if the Learning Resources are zero, then student learning achievement will be worth 40.451, the regression coefficient of variable X1 is positive at 0.236 and the regression coefficient of variable X2 is positive at 0.398, that every class management and Learning resources increase by one unit will cause an increase in learning achievement of 0.236 and 0.398 one unit. This means that the influence is a positive influence.